Evaluation of the Injana claystone from Central Iraq for the brick industry - Awadh, Salih Mohammad; Awad, Ali Mutlag (Kuwait Journal of Science, 2021)
The aim of this study is to suggest an ancient clay for the manufacturing bricks as an alternative to the recent clays that are considered as agricultural lands. The Late Miocene claystone bed in the Injana Formation at middle of Iraq was targeted through 18 exposed sections that were sampled by using the trench sampling method. The samples are characterized by mineralogy dominated by quartz (36.4%) followed by calcite (32.8%), feldspar (2.6%), gypsum (0.9%) and dolomite (0.7%) in addition to non-clay minerals composed of kaolinite (10.1%), illite (7.7%), chlorite (6.7%), palygorskite (6.0%) and montmorillonite (1.2%). New Thermal mineral phases were formed at 950°C include diopside (35.6%), quartz (21.6%), wollastonite (11.4%), akermanite (11.1%), and gehlenite (2.3%). The engineering tests of the raw material showed the plasticity according to the Atterberg limits varies from low to high, low volumetric and linear shrinkage during drying and firing with a temperature at 950°C. The raw material produced bricks with 156 kg/cm2 uniaxial compressive strength, 23.4% water absorption and nil to low efflorescence. The results indicate the success of the Late Miocene clay in the manufacture of bricks for medium to high quality within the A and B category based on the Iraqi standard specification No.25 in 1993.